Mean reversion of the fiscal conduct in 24 developing countries. - Baharumshah, Ahmad Zubaidi; Lau, Evan (Blackwell Publishing Ltd, 2010)

(untitled)
In this paper, we examine the mean reverting behaviour of fiscal deficit by analysing the fiscal position of 24 developing countries. Using annual data over the period 1970–2003 and the series-specific panel unit root test developed by Breuer et al. (Oxford Bulletin of Economics and Statistics, Vol. 64 (2002), pp. 527–546), we found the budget process for most developing countries fails to satisfy the strong-form sustainability condition. Further investigation shows the budget process for a majority of the countries is on a sustainable path (weak form) when a one-time, structural break is allowed in the model. Therefore, our empirical results suggest that the budget process in most of the sample countries is in accordance with the intertemporal budget constraint.